2012
DOI: 10.1152/japplphysiol.01618.2011
|View full text |Cite
|
Sign up to set email alerts
|

Airway closure on imaging relates to airway hyperresponsiveness and peripheral airway disease in asthma

Abstract: . Airway closure on imaging relates to airway hyperresponsiveness and peripheral airway disease in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 42 publications
(61 reference statements)
1
53
1
Order By: Relevance
“…115,118,119 Intriguingly, the degree of baseline heterogeneity appears to predict the severity of airway hyperresponsiveness in adults and children with asthma, [120][121][122] in a way that differs from subjects with COPD. 114,124 Further studies have identified relationships between heterogeneity and symptom control 125 ; clinical stability 118 ; and response to inhaled corticosteroids. 114,124 Further studies have identified relationships between heterogeneity and symptom control 125 ; clinical stability 118 ; and response to inhaled corticosteroids.…”
Section: Inert Gas Washout For Measurement Of Ventilation Inhomogeneitymentioning
confidence: 99%
“…115,118,119 Intriguingly, the degree of baseline heterogeneity appears to predict the severity of airway hyperresponsiveness in adults and children with asthma, [120][121][122] in a way that differs from subjects with COPD. 114,124 Further studies have identified relationships between heterogeneity and symptom control 125 ; clinical stability 118 ; and response to inhaled corticosteroids. 114,124 Further studies have identified relationships between heterogeneity and symptom control 125 ; clinical stability 118 ; and response to inhaled corticosteroids.…”
Section: Inert Gas Washout For Measurement Of Ventilation Inhomogeneitymentioning
confidence: 99%
“…Similarly, CT imaging has demonstrated greater changes in peripheral airways after methacholine challenge in asthmatics [31]. Other studies using multiple breath nitrogen washout and imaging [32] have shown an increase in ventilation heterogeneity in individuals with hyper reactivity to methacholine which appeared to be independent of changes in airway resistance [33]. Modelling studies indicate that the most marked effect of airways constriction on FeNO50 is most likely to occur in generations 10-15 and that constriction in smaller airways is likely to increase FeNO50 due to interference with the NO back diffusion effect [34].…”
Section: Discussionmentioning
confidence: 97%
“…Tomographic imaging methods include hyperpolarised noble gas magnetic resonance imaging (MRI) (e.g. helium-3 or xenon) [2], positron emission tomography [3], single photon emission computed tomography (CT) [4,5] and oxygen enhanced MRI [6], where the distribution of a tracer gas is imaged. Inert-gas washout tests are based on the simple principle that regions of the lung that ventilate poorly or not at all (i.e.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The main contribution of imaging studies to our understanding of ventilation distribution in asthma is the revelation of the presence of large and dramatic ventilation defects [3][4][5]14], caused presumably by both localised airway closure and severe airway narrowing. There has been very little analysis of the distribution of ventilation, i.e.…”
Section: @Erspublicationsmentioning
confidence: 99%
See 1 more Smart Citation